Coated articles with enhanced oxidation resistance

JP2024533684A5Inactive Publication Date: 2025-04-16OERLIKON SURFACE SOLUTIONS AG PFAFFIKON
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024518509
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-09-23
Filing Date
2022-09-22
Publication Date
2025-04-16
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing transition metal boride coatings exhibit poor oxidation resistance at high temperatures, limiting their application in high-performance components like mechanical elements in aircraft engines.

Method used

A coated article with a protective layer comprising transition metal borides and a dopant element silicon, promoting the formation of a dense Si-rich scale that enhances oxidation resistance, particularly at temperatures ranging from 800°C to 1500°C.

Benefits of technology

The coated article achieves significantly improved oxidation resistance, with parabolic rate constants reduced to 10^-9 to 10^-13 kg^2 m^-4 s^-1 at 1100°C, forming a dense Si-enriched oxide scale that maintains structural integrity under high-temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention relates to a coated article comprising a coated surface, the coated surface comprising a substrate and a coating system, the coating system comprising at least one protective layer comprising one or more transition metal borides and a dopant element, - the protective layer is of formula TM x B y S q wherein TM is one or more transition metal elements selected from the group formed by chromium, Cr, and hafnium, Hf; Si is silicon and is present in the protective layer as a dopant element; B is boron; x is the concentration in atomic percentage of TM in the protective layer; y is the concentration in atomic percentage of B in the protective layer; q is the concentration in atomic percentage of Si in the protective layer; and x+y+q=1, 0.15≦x≦0.33, 0.40≦y≦0.67, and 0.1≦q≦0.40; the atomic concentration ratio of boron to transition metal in the protective layer is 2 or more, i.e. y / x≧2; The protective layer exhibits an AlB2 crystal structure.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to coated articles and methods of making coated articles of the present invention. The coated articles of the present invention exhibit improved oxidation resistance properties, comprising a substrate and a coating system, wherein the coating system comprises a transition metal boride coating layer capable of forming an oxidation barrier coating layer, or wherein the coating system comprises an oxidation barrier coating layer and a transition metal boride layer capable of forming an oxidation barrier coating layer. A transition metal boride coating layer capable of forming an oxidation barrier coating layer comprised of one or more borides of one or more transition metals, wherein the transition metals are chromium and / or hafnium, and the layer comprises silicon as a dopant.

[0002] FIELD OF THEINVENTION Transition metal (TM) borides are known for their heat-resistant properties with melting temperatures above 3000 °C, wide phase stability, or high thermal conductivity as well as strong thermal shock resistance. Due to the increasing interest in the sustainable use of materials and the longevity of high-performance components, e.g. machine elements of aero engines, TM boride-based materials have been proposed as a new class of protective thin films. Therefore, the stability of such coatings, especially at high temperatures, is desirable and strategies have been developed to improve the poor oxidation resistance of such coatings. [Background technology]

[0003] When oxidizing diboride-based bulk ceramics, typically an oxide scale with a glassy top B2O3 (boria) layer is formed, as known from TiB2, ZrB2, and HfB2. In detail, three different regimes can be distinguished: (i) a low-temperature regime, typically below 900 °C to below 1000 °C, where a crystalline metal oxide layer with a more or less dense boria layer on top is obtained, (ii) a second regime up to 1600 °C to 1800 °C with the first evaporation of the top B2O3, and (iii) a final regime above 1800 °C, where the volatile evaporation of boria adjacent to the porous metal oxide dominates. However, environmental conditions such as atmospheric humidity or flow conditions can also affect the oxide scale formation of TM borides. It is known that the presence of water vapor accelerates the formation of volatile boric acid (HBO2), promoting the volatility of boria and therefore reducing the oxidation resistance.

[0004] To date, only alumina- and silica-based oxide scales have been developed to sustain long-term oxidation at high temperatures (>1000°C), with a growth rate of approximately 10% at 1100°C. -10 kg 2 It is known to provide a sufficiently low parabolic rate constant in the order of m-4s-1. Summary of the Invention [Problem to be solved by the invention]

[0005] It is a primary object of the present invention to provide a coated article having a coated surface which exhibits the highly advantageous properties of transition metal borides, but at the same time exhibits greater oxidation resistance at elevated temperatures, particularly at temperatures in the range of 800°C to 1500°C. [Means for solving the problem]

[0006] Description of the invention The above object is achieved by providing a coated article and a method for producing the coated article according to the invention, in particular a coated article according to claims 1-10 and a method in particular according to claims 11-16.

[0007] The coated article of the present invention comprises a coated surface, the coated surface comprising a substrate and a coating system, the coating system comprising at least one protective layer comprising one or more transition metal borides and a dopant element; The protective layer is of the formula TM x B y S q (In the formula, TM is one or more transition metal elements selected from the group formed by chromium, Cr, and hafnium, Hf; Si is silicon, which is present in the protective layer as a dopant element; B is boron, x is the concentration in atomic percentage of TM in the protective layer, y is the concentration in atomic percentage of B in the protective layer, q is the concentration of Si in the protective layer in atomic percentage, x+y+q=1, 0.15≦x≦0.33, 0.40≦y≦0.67, and 0.1≦q≦0.40) and having a chemical elemental composition defined by the atomic concentration ratio of boron to the transition metal in the protective layer is 2 or more, i.e., y / x≧2; The protective layer exhibits an AlB2 crystal structure.

[0008] It is important to note that oxygen or oxygen and carbon and / or other elements (eg, argon) may be unintentionally present in the protective layer as trace elements.

[0009] According to a preferred embodiment of the coated article according to the invention, the content of Si, denoted by q, is higher than 0.1, which makes it possible to achieve a surprisingly significant further increase in oxidation resistance by promoting the formation of a dense Si-rich scale. More preferably, q is higher than 0.2. Even more preferably, q is higher than 0.3.

[0010] According to a further preferred embodiment of the coated article according to the invention, the protective layer is disposed as the outermost layer of the coating system or as close as possible to the outermost layer (e.g., immediately adjacent to the outermost layer) to promote the formation of a dense Si-enriched scale.

[0011] According to a further preferred embodiment of the coated article according to the invention, the coating system comprises an oxide layer formed as the outermost layer of the coating system, the oxide layer comprising or consisting of silicon and oxygen, preferably silicon dioxide, SiO2.

[0012] In the context of the present invention, the oxide layer is, in one preferred embodiment, an oxide layer comprising or consisting of a Si-rich scale (also referred to in the context of this specification as dense Si-rich scale) promoted by the Si contained in the protective layer, which diffuses towards the outermost surface of the coating system and reacts with oxygen available at the outermost surface of the coating system to form a Si-rich scale.

[0013] When the coated article of the present invention comprises an oxide layer as described in one of the preferred embodiments above, the protective layer is preferably disposed directly beneath the oxide layer.

[0014] The thickness of the oxide layer is preferably 50 nm or more and 5000 nm or less. The protective layer preferably exhibits a separate crystalline Si phase that is visible in the XRD spectrum of said protective layer at 2θ angles of 28.44° and / or 47.3°. This separate crystalline Si phase can be produced, for example, by subjecting the protective layer to a process that oxidizes the protective layer, such as an annealing step or any step that results in oxidation, so that a separate crystalline Si phase is formed in the protective layer and can be detected after oxidation. The inventors believe that the formation of this separate crystalline Si phase promotes the formation of Si-rich scale as described above. In the context of the present invention, Si-rich scale should be understood in particular as a Si-O-containing oxide layer.

[0015] Preferably, the oxidation kinetics of the protective layer is 10 at a temperature of 1100° C. -9 kg 2 m -4 s -1 From 10 -13 kg 2 m -4 s -1 The range is up to.

[0016] In the context of the present invention, preferred substrates comprise or consist of one or more materials selected from the group formed by steel, cemented carbide, Inconel, Hastelloy, Waspaloy, superalloy, Ti-containing materials, oxides, oxide-oxide ceramics, SiC-containing materials, carbon-based materials, yttria-stabilized zirconia.

[0017] The method of manufacturing the coated article of the present invention according to any of the above-described embodiments preferably includes one or more steps in which the protective layer is formed by using a coating process.

[0018] According to a preferred embodiment of the method for producing a coated article according to the invention, said method comprises at least the following steps: at least one protective layer is formed by using a coating process, The oxide layer and / or separate crystalline Si phase in the protective layer is produced by a heat treatment carried out after the coating process, the AlB2 crystal structure being already produced during the coating process and being maintained during and after the heat treatment, including an annealing process, in which the heat treatment is carried out at a process temperature in the range of 800 ° C - 1500 ° C, preferably in the range of 1100 ° C - 1300 ° C.

[0019] Preferably, the coating process used in any of the methods for forming a protective layer for producing a coated article according to the present invention comprises: -physical vapor deposition (PVD) technology, and / or - Chemical vapor deposition (CVD) technology, and / or -thermal or plasma assisted chemical vapor deposition (TA-CVD or PA-CVD) This is done by using

[0020] According to a preferred embodiment, the coating process for producing the protective layer is carried out such that one or more targets containing silicon are used as coating raw materials for providing the desired silicon concentration in the oxidation barrier coating layer during the coating process, which is carried out by using a physical vapor deposition (PVD) technique, preferably a type arc PVD technique or a sputtering PVD technique, such as magnetron sputtering or high power impulse magnetron sputtering (HiPIMS).

[0021] According to another preferred embodiment, the coating process for producing the protective layer is carried out in such a way that one or more gas streams containing silicon are used as coating raw materials for providing the desired silicon concentration in the oxidation barrier coating layer during the coating process, which is carried out by using a physical vapor deposition (PVD) technique, preferably a type arc PVD technique or a sputtering PVD technique, such as magnetron sputtering or high power impulse magnetron sputtering (HiPIMS).

[0022] Description of some embodiments of the present invention In order to explain the present invention in more detail, some examples of coating systems and methods for producing coated articles according to the present invention and for producing coating systems are described below with the help of Figures 1 to 7. The contents of these examples and figures should not be understood as limitations of the present invention, but as embodiments or illustrations of the present invention. [Brief description of the drawings]

[0023] [Figure 1] (a) All deposited coating chemical compositions determined by ICP-OES. The dashed line represents the B / TM ratio of the stoichiometric TMB2 coating material. The numbers indicate the amount of Si platelets used to obtain the composition. (b) Hardness determined using nanoindentation for all as-deposited coatings. [Diagram 2] Mass change during dynamic oxidation performed in a TG system using synthetic air and a heating rate of 10 K / min. The dashed lines represent the two-component coatings, CrB2.27 (a) and HfB2.36 (b). The dashed and dotted lines represent the TM-Si-B2±z coatings with various Si contents. The solid lines represent the TM-Si-B2±z coatings investigated in more detail, Cr0.26Si0.16B0.58 (a) and Hf0.21Si0.18B0.61 (b). [Diagram 3] Mass gain during isothermal oxidation at 900 °C (a) and 1100 °C (b). [Figure 4] XRD analysis of Cr0.26Si0.16B0.58 (a) and Hf0.21Si0.18B0.61 (b). The upper spectrum represents the deposited state for each system, the middle after isothermal oxidation at 900 °C and the lower after oxidation at 1100 °C. In addition, the dashed lines in the as-deposited state represent the spectrum of the binary coating. The solid reference lines with hexagons above them represent the AlB2 prototype structure of each diboride. [Diagram 5] SEM fracture cross sections of Cr0.26Si0.16B0.58 (a) and Hf0.21Si0.18B0.61 (b) after isothermal oxidation at 900 °C (left) and 1100 °C (right). The white dashed lines represent the different interfaces. [Figure 6] TEM study of Hf0.21Si0.18B0.61 oxidized at 1200 °C for 3 h in ambient air. (a) BF image including the entire coating and the oxide scale formed on top. (b) EDX line scan through the entire thickness as indicated by the arrow in (a). (c) SAED image of the oxide scale, and (d) zoomed-in interface between the remaining coating and the oxide scale. [Figure 7]Cr0.26Si0.16B0.58 oxidized at 1200 °C for 3 h in ambient air. High angle annular dark field (HAADF) image (a) and BF image (b) of the entire remaining coating including the substrate at the bottom and the oxide scale on top. (c) STEM image and elemental EDX map (d) of the region indicated by the dashed lines in (a) and (b) and the corresponding BF image (e) through the entire coating thickness as indicated by the arrows in (a). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] In the context of the present invention, Cr-B and Hf-B based coatings were investigated with respect to their thermal stability in oxidizing environments.

[0025] During the investigation of HfB2 coatings, a similar oxidation behavior was observed for the investigated HfB2 coatings compared to their bulk ceramic counterparts which form a layered scale, exhibiting a dense scale at 900 °C with a rate constant kp of 1.39 10 -9 kg 2 m -4 s -1 A parabolic rate law was traced.

[0026] TM-Si-B 2±z (TM:Cr and / or Hf) based thin films were deposited by PVD magnetron sputtering utilizing CrB2 and HfB2 targets (Plansee Composite Materials GmbH). Silicon was added to the deposition by adding single crystal Si platelets onto the sputter racetrack of the target. By varying the number of pieces, TM-Si-B 2±z The Si content was adjusted in the coating. The targets were operated in DC mode with a current of 0.5 A (0.4 A for CrB2) in a pure argon atmosphere at a working pressure of 0.56 Pa. The thin films were made of polycrystalline Al2O3 (20 × 7 × 0.38 mm 3 ) and sapphire (10×10×0.53 mm 3) substrate with a target to substrate distance of 90 mm. For all depositions, a substrate temperature of 550° C. and a bias potential of −40 V were used.

[0027] For stoichiometric determination, samples were analyzed by liquid inductively coupled plasma optical emission spectroscopy (ICP-OES) after acid digestion. To exclude silicon contamination from the substrate, only samples on Al2O3 wafers were investigated. All chemicals were of the highest purity available, ultrapure water with resistivity of 18.2 MΩ was obtained by a Barnstead EASYPURE II water system (Thermo Fisher Scientific, USA), and single-element ICP standards and concentrated acids were purchased from Merck (Germany). Samples were cut into 5 × 5 mm pieces and digested in triplicate with a mixture of 0.5 mL HNO3 and 0.5 mL HF in a Falcon tube by heating to 80 °C for 10 min. Afterwards, samples were diluted to a volume of 20 mL with H2O and europium was added as an internal to obtain a final concentration of 1 μg / g europium. Samples were measured on an iCAP 6500 RAD (Thermo Fisher, USA) with an ASX-520 autosampler (CETAC Technologies, USA) using an HF-resistant sample introduction kit consisting of a Miramist nebulizer (Burger Research, USA), an alumina injection tube and a PTFE spray chamber. Background-corrected luminescence signals were quantified using matrix-adjusted external calibration standards.

[0028] Mechanical properties were assessed by nanoindentation using an Ultra Micro Indentation System (UMIS) with a Berkovich diamond tip (all measurements were performed on sapphire substrates). For each specimen, 30 idles with different applied loads (3-45 mN) were performed and their load-displacement curves were analyzed after Oliver and Pharr. The Poisson's ratio to calculate Young's modulus was taken from Reference: V. Moraes, H. Riedl, C. Fuger, P. Polcik, H. Bolvardi, D. Holec, PH Mayrhofer, Ab initio inspired design of ternary boride thin films, Sci. Rep. 8 (2018) 9288.

[0029] To study the oxidation behavior of the deposited coatings, a Thermo-Gravimetric Analysis (TGA) system equipped with a rhodium oven (Netzsch STA 449 F1) was used. The TGA system has a resolution of 0.1 μg, yielding a limit of about 10 μg to detect significant effects. The polycrystalline Al2O3 substrates were weighed before and after deposition to determine the weight of the coating and subsequently placed in customized crucibles. The dynamic oxidation treatment (steady temperature increase between RT and 1400 °C) was carried out under a flowing flow of synthetic air (50 ml / min) and helium (20 ml / min) as required to protect the scale (heating rate of 10 K / min). For the isothermal oxidation, the synthetic air was only flowing through the furnace during the isothermal step. A baseline measurement with an empty crucible was carried out for each run. Furthermore, the oxidation treatment in ambient air at 1200 °C was carried out in a standardized chamber box furnace, with the coated substrates placed on fireclay tiles.

[0030] X-ray diffraction (XRD) analysis shows that Cu-K αA Panalytical Empyrean diffractometer equipped with a radiation source (wavelength λ = 1.5418 Å) was used in the Bragg Brentano geometry. A scanning electron microscope (SEM, FEI Quanta 250 FEGSEM operated at 5 keV) was used to study the morphology and the thickness of the oxide scale. Furthermore, transmission electron microscopy (TEM, FEI TECNAI F20, equipped with a field emission gun and operated at an accelerating voltage of 200 kV) was performed for a more detailed investigation of the oxidized samples.

[0031] The chemical composition of the synthesized coating obtained by ICP-OES is shown in Figure 1a, showing the B / TM ratio as a function of silicon content (the numbers next to the symbols refer to the number of Si platelets). The stoichiometry is 2+z Coating (CrB 2.27 and HfB 2.36 ) showing a metal deficiency. The silicon content increases with increasing number of Si platelets placed on the racetrack. The B / TM ratio remained approximately constant for Cr, but for the Hf-based coatings no clear trend is observed as the B / TM ratio is highest for the lowest amount of Si platelets.

[0032] In Figure 1b, TM-Si-B 2±z The effect of Si on the mechanical properties (hardness and Young's modulus) of the two-component coatings is summarized. 2.27 25.1±2.1GPa, HfB 2.36 The hardness values ​​of 48.7±2.7 GPa for Cr and Hf alloyed films show a decrease in hardness. For about 15 at. % Si, the hardness is in the range of 22 GPa and 32 GPa for Cr- and Hf-based coatings, respectively. The hardness and Young's modulus of the coatings investigated in more detail below are 0.26 S 0.16 B 0.58 For Hf, H = 22 ± 2.1 GPa and E = 410 ± 31 GPa. 0.21 S 0.18 B 0.61For , H = 32 ± 2.2 GPa and E = 468 ± 34 GPa.

[0033] In Figure 2, the mass change (percentage of the initial mass) as a function of temperature during dynamic oxidation is plotted. The dashed line indicates the binary TM-B 2±z The solid lines correspond to the TM-Si-B coating, while the solid lines indicate the Si-alloyed coatings investigated in more detail herein. Furthermore, the dashed and dotted lines correspond to the TM-Si-B coatings with other Si contents. 2±z The mass signal is constant up to a certain temperature (oxidation onset temperature), indicating that as oxidation proceeds, no oxide scale forms and the mass increases subsequently. The oxidation onset temperature is 2.27 At 610℃, HfB 2.36 At 800° C. above this onset temperature, the mass increases until the coating is fully oxidized, after which it decreases due to volatilization of B2O3 (typically above 1100° C.).

[0034] To further evaluate and understand these trends in mass gain measured during dynamic oxidation, isothermal oxidation treatments were performed for 1 h at two temperatures: 900 °C and 1100 °C. The isothermal oxidation at 900 °C was carried out to obtain the Hf 0.21 S 0.18 B 0.61 As already suggested by the results shown in Fig. 2a, the Cr 0.26 S 0.16 B 0.58 shows a mass increase below the resolution limit of the TG system and therefore the growth kinetics is strongly retarded. To oxidize the coating material at 1100 °C, TM-Si-B 2±z The mass gain of the coating is very low (again, within the resolution limit of the TG system), thus suggesting a very slow oxide growth rate. Visual inspection shows a well-adherent and dense oxide scale. Due to the resolution limit of the TG system, the kinetics of the oxide growth are estimated to be 1·10 -11 kg 2 m -4 s -1 The parabolic rate constant (k p ) could only be determined.

[0035] To further understand the dependence of oxide scale formation on temperature, comparative structural analysis by XRD was carried out for as-deposited and oxidized conditions for isothermal treatments at 900 °C and 1100 °C (Figure 4). All binary TM-B 2±z The coating is crystallized in the AlB2 prototype, shown in dashed lines. The AlB2 structure type is defined by the SG191 structure (P6 / mmm, Pearson symbol hP3) which gives a boron sheet (arrangement of atoms) covalently bonded between the metal layers with a ratio of B / TM=2. TM-Si-B 2±z The coatings are plotted as solid black lines from top to bottom in the as-deposited state and oxidized at 900 and 1100 °C, respectively. With the addition of Si, the main peak gradually broadens. 0.26 S 0.16 B 0.58 In the case of Cr, a peak shift to higher 2-theta diffraction angles is observed (Figure 4a). 0.26 S 0.16 B 0.58 In the case of Hf, oxidation at 900 °C and 1100 °C leads to phase separation of elemental Si (Si peak in Fig. 4a). Furthermore, the CrB2 peaks shift back to their normal position and also show a decrease in FWHM, indicative of recrystallization. 0.21 S 0.18 B 0.61 In the case of , the structural analysis in the oxidized state does not suggest any decomposition or recrystallization processes. However, a strong monoclinic HfO2 peak is visible at 900 °C, but it almost disappears at 1100 °C.

[0036] Oxide scale formed, Cr 0.26 S 0.16 B 0.58 (a) and Hf 0.21 S 0.18 B 0.61To gain further insight into the SEM cross-sections in (b), the isothermally oxidized coatings are shown in Figure 5. All left hand micrographs show coatings oxidized at 900 °C, while the right hand cross-sections have been oxidized at 1100 °C (see Figure 3 for duration). The dashed lines highlight the interface between substrate and coating, while the dotted lines indicate interfaces between scale and coating or between different types of oxide scales. For all coatings, remaining unoxidized areas can be identified.

[0037] Additional isothermal oxidation treatments have been performed in a conventional furnace in ambient air at higher temperatures and for longer durations. Figure 6 shows Hf oxidized on a sapphire substrate at 1200 °C for 3 h. 0.21 S 0.18 B 0.61 The TEM analysis of the oxide scale is shown in Figure 6c. The bright field (BF) clearly shows the remaining coating from bottom to top, followed by a bright but very thin oxide scale on top. The thickness as deposited coating is reduced by 100 nm, from 2.4 μm to 2.3 μm after oxidation, while the oxide scale itself gains a thickness of 400 nm. The oxide scale is clearly visible in the selected area electron diffraction (SAED) analysis (Figure 6c). I ) appears amorphous, has an AlB2 structure, and has decreasing column size from top to bottom (Fig. 6c II The EDX line scan shows a very sharp interface towards the sapphire substrate and an equal distribution of Hf, B and Si throughout the remaining coating thickness. Furthermore, the line scan suggests boron enrichment at the coating-oxide interface, as well as that the oxide scale is dominated by silicon with some addition of boron. However, the precision of EDX for quantifying boron is very low, so the resulting composition must be interpreted with caution. Si and Hf also overlap in the EDX spectrum, causing an additional overestimation of Hf to the cost of Si. Additional EELS analysis suggests that the boron content in the oxide scale is significantly lower than assessed by EDX. Hf determined using EELS 0.21 S 0.18 B 0.61The chemical composition of the oxide scale on the 0.46 B 0.03 O 0.51 It is.

[0038] In contrast, Cr oxidized at 1200°C for 3 hours 0.26 S 0.16 B 0.58 have a rather different appearance during TEM analysis (Figure 7). Firstly, the high angle annular dark field (HAADF, see Figure 7a) as well as the bright field image (see Figure 7b) show that the remaining coating is fully recrystallized and shows large globular grains with some voids in between. Furthermore, the HAADF image shows light and dark grains representing areas of high atomic number (light) and low atomic number (dark). Together with the EDX line scan (Figure 7c), Cr- and Si-enriched grains can be identified. Moreover, further XRD analysis clearly proves CrB2 adjacent to the elemental Si peak similar to the results presented in Figure 4. Thus, the light areas represent CrB2 and the dark areas are Si-enriched grains. Moreover, Cr and O overlap in the EDX spectrum, causing an overestimation of O in CrB2. Nevertheless, on top of the resolved microstructure, a very thin and dense oxide scale can also be found. The EDX maps (Figure 7d and corresponding STEM and BF images in Figure 7e with the respective elemental maps of Cr, O, B, and Si, respectively) nicely show that the oxide scale consists of two layers with Cr2O3 crystals on the outside and silica at the interface between the coating and the oxide scale (see the light orange area in the Si map). Due to the recrystallized remaining coating, the surface is rather rough and the oxide scale thickness varies between 180 nm and 750 nm, showing an average thickness of 400 ± 137 nm. The remaining coating thickness was close to the original thickness of about 2.6 μm, but showed a much higher standard deviation due to the roughness.

[0039] The results clearly demonstrate the positive effect of silicon when alloyed (doped) into TM boride-based coatings to increase oxidation resistance, however this effect is only achieved if the coating (in the context of the present invention, the protective layer) contains a certain amount of Si to enable the formation of a dense Si-rich scale according to the invention as explained above.

Claims

1. 1. A coated article comprising a coated surface, the coated surface comprising a substrate and a coating system, the coating system comprising at least one protective layer comprising one or more transition metal borides and a dopant element; said protective layer having the formula TM x B y S q wherein TM is one or more transition metal elements selected from the group formed by chromium, Cr, and hafnium, Hf; Si is silicon and is present in the protective layer as the dopant element; B is boron; x is the concentration in atomic percentage of TM in the protective layer; y is the concentration in atomic percentage of B in the protective layer; q is the concentration in atomic percentage of Si in the protective layer; and x+y+q=1, 0.15≦x≦0.33, 0.40≦y≦0.67, and 0.1≦q≦0.40; the atomic concentration ratio of boron to the transition metal in the protective layer is greater than or equal to 2, i.e. y / x≧2; - the protective layer is AlB 2 Showing the crystal structure, A coated article comprising a coated surface.

2. 2. The coated article of claim 1, wherein q is greater than 0.

1.

3. 3. The coated article of claim 2, wherein q is greater than 0.

2.

4. 4. The coated article of claim 3, wherein q is greater than 0.

3.

5. The coated article of claim 1 , wherein the protective layer is disposed as the outermost layer of the coating system.

6. The coating system comprises an oxide layer formed as the outermost layer of the coating system, the oxide layer comprising or consisting of silicon and oxygen, preferably silicon dioxide, SiO 2 The coated article of claim 1 comprising:

7. 7. The coated article of claim 6, wherein said protective layer is disposed directly beneath said oxide layer.

8. The coated article of claim 6, wherein the thickness of the oxide layer is in the range of 50 nm to 5000 nm.

9. 7. The coated article of claim 6, wherein the protective layer exhibits a distinct crystalline Si phase that is visible in the XRD spectrum of the protective layer at 2θ angles of 28.44° and / or 47.3°.

10. The oxidation rate of the protective layer is 10 -9 kg 2 m -4 s -1 From 10 -13 kg 2 m -4 s -1 The coated article of claim 1, wherein the thickness of the coated article is in the range of 100 nm to 150 nm.

11. 2. The coated article of claim 1, wherein the substrate comprises or consists of one or more materials selected from the group formed by steel, cemented carbide, Inconel, Hastelloy, Waspaloy, superalloy, Ti-containing materials, oxides, oxide-oxide ceramics, SiC-containing materials, carbon-based materials, yttria stabilized zirconia.

12. - said at least one protective layer is formed by using a coating process; A method for producing the coated article of claim 1 .

13. - said at least one protective layer is formed by using a coating process, - the oxide layer and / or the separate crystalline Si phase in the protective layer are produced by a heat treatment carried out after the coating process, and the AlB 2 comprising an annealing process in which the crystalline structure is already produced during the coating process and is maintained during and after said heat treatment, said heat treatment being carried out at a process temperature in the range of 800°C to 1500°C, preferably in the range of 1100°C to 1300°C; A method for producing the coated article of claim 6.

14. The coating process comprises: - Physical Vapour Deposition (PVD) technology, and / or Chemical Vapor Deposition (CVD) technology, and / or - Thermal or Plasma-Assisted Chemical Vapor Deposition (TA-CVD or PA-CVD) The method according to claim 12 or 13, which is carried out by using

15. 15. The method according to claim 14, characterized in that the coating process is carried out such that one or more targets comprising silicon are used as coating raw materials for providing the desired silicon concentration in the oxidation barrier coating layer during the coating process, which is carried out by using a physical vapor deposition (PVD) technique, preferably a type arc PVD technique or a sputtering PVD technique, such as magnetron sputtering or high power impulse magnetron sputtering (HiPIMS).

16. 15. The method according to claim 14, characterized in that the coating process is carried out such that one or more gas streams containing silicon are used as coating raw materials for providing the desired silicon concentration in the oxidation barrier coating layer during the coating process, which is carried out using a physical vapor deposition (PVD) technique, preferably an arc PVD technique or a sputtering PVD technique, such as magnetron sputtering or high power impulse magnetron sputtering (HiPIMS).